2022
DOI: 10.5694/mja2.51661
|View full text |Cite
|
Sign up to set email alerts
|

COVID ‐19 in New South Wales children during 2021: severity and clinical spectrum

Abstract: Objectives: To describe the severity and clinical spectrum of coronavirus disease 2019 (COVID‐19) in children during the 2021 New South Wales outbreak of the Delta variant of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Design, setting: Prospective cohort study in three metropolitan Sydney local health districts, 1 June – 31 October 2021. Participants: Children under 16 years of age with positive SARS‐CoV‐2 nucleic acid test results admitted to hospital or managed by the Sydney Children’s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…In a study from Thailand human bocavirus was the third most common pathogen detected, after rhinovirus and RSV, accounting for 12% of all cases ( 46 ). SARS-CoV-2, the cause of the COVID-19 pandemic, also infects children, but it rarely causes severe disease ( 47 ) and this risk is further reduced by vaccination ( 48 ). Four other coronaviruses are established human pathogens, but only cause mild cold like symptoms ( 49 ).…”
Section: Common Causes Of Community-acquired Pneumoniamentioning
confidence: 99%
“…In a study from Thailand human bocavirus was the third most common pathogen detected, after rhinovirus and RSV, accounting for 12% of all cases ( 46 ). SARS-CoV-2, the cause of the COVID-19 pandemic, also infects children, but it rarely causes severe disease ( 47 ) and this risk is further reduced by vaccination ( 48 ). Four other coronaviruses are established human pathogens, but only cause mild cold like symptoms ( 49 ).…”
Section: Common Causes Of Community-acquired Pneumoniamentioning
confidence: 99%
“…Phoebe Williams and her colleagues 11 investigated COVID‐19 severity and outcomes in Sydney children during the Delta SARS‐CoV‐2 variant wave in 2021. Most infections were asymptomatic or mild.…”
Section: Our Best Original Research Articles In 2022mentioning
confidence: 99%
“…Phoebe Williams and her colleagues 11 In the largest published post-marketing analysis of the safety of the Comirnaty and Vaxzevria vaccines, Lucy Deng and colleagues 13 analysed data from online AusVaxSafety surveys of more than three million people aged 16 years or more. The authors found that adverse events were more frequently reported by people with underlying medical conditions, including a history of anaphylaxis.…”
mentioning
confidence: 99%
“…The few Australian publications on COVID‐19 in children have reported its often mild nature, but have described only limited numbers of children (36 to 384 per article) infected during 2020 with the original SARS‐CoV‐2 strain or one of its early variants 3‐6 . In this issue of the MJA , Williams and colleagues provide welcome information about infections with the Delta SARS‐CoV‐2 variant during June–October 2021 in 17 474 New South Wales children under 16 years of age, including 11 985 managed by the Sydney Children’s Hospital Network virtual care team 7 . In a sample including all 165 children admitted to hospital for medical reasons (1.3% of confirmed infections) and a random selection of those who received virtual team care, 110 of 509 children (22%) were asymptomatic, and the others had mild symptoms.…”
mentioning
confidence: 99%
“… 3 , 4 , 5 , 6 In this issue of the MJA , Williams and colleagues provide welcome information about infections with the Delta SARS‐CoV‐2 variant during June–October 2021 in 17 474 New South Wales children under 16 years of age, including 11 985 managed by the Sydney Children’s Hospital Network virtual care team. 7 In a sample including all 165 children admitted to hospital for medical reasons (1.3% of confirmed infections) and a random selection of those who received virtual team care, 110 of 509 children (22%) were asymptomatic, and the others had mild symptoms. Only fifteen NSW children with confirmed infections (0.09%) required intensive care, including seven with multisystem inflammatory syndrome in children (MIS‐C).…”
mentioning
confidence: 99%